Peran Pendidikan Agama Islam dalam Membangun Toleransi Antarumat Beragama di SMKN Pembangunan Pertanian Rea Timur Polewali Mandar - Akmal Hidayat; Harbiah Idrus; Yulmiati Yulmiati; Ayyub Daeng Pananrang; Syarifah Nadila Andriani; Yusriah Yusriah (JITU Jurnal Ilmiah Tarbiyah Umat, 2025)
Islamic Religious Education plays a significant role in fostering tolerance in multicultural vocational school environments. This study aims to describe how Islamic Religious Education learning at SMKN PP Rea Timur contributes to building mutual respect among religious communities. The study uses a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, participatory observations, and curriculum documentation. Data were analyzed using reduction and triangulation techniques. The results show that a contextual teaching approach encourages students to understand differences, develop empathy, and practice tolerance in daily life. These findings emphasize the importance of strengthening inclusive religious values in vocational education to promote social harmony.